PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI LISTRIK DINAMIS DI KELAS IX SMP NEGERI 7 SUNGAI RAYA - Arlisa Arlisa; Dewi Fajar Saputri; Boisandi Boisandi (Universitas Tanjungpura, 2020)
This study aims to obtain an objective clarity regarding the application of discovery learning models to students' science process skills in dynamic electrical material for class IX students of SMP Negeri 7 Sungai Raya. This research method uses the Quasi Experiment Design method with the research design is Posttest-Only Nonequivalent Groups. Data collection techniques are essay tests to measure students' science process skills. The population in this study were all grade IX students of SMP Negeri 7 Sungai Raya consisting of 4 classes. The sample in this study were students of SMP Negeri 7 Sungai Raya in class IX B and class IX C in the odd semester of the 2019/2020 school year, taken by cluster random sampling. Analysis of the data description using the average equation (mean), analysis of the hypothesis test using the U Maan Whitney test. The results of this study indicate that 1) the students' science process skills after applying the direct learning model to the dynamic electrical material of class IX students of SMP Negeri 7 Sungai Raya is classified as not good at 62.67; 2) students' science process skills after the discovery learning model applied to the dynamic electrical material of class IX students of SMP Negeri 7 Sungai Raya is classified as good, amounting to 81.07; 3) there are differences in the science process skills of students who are taught using discovery learning models and students who are taught using direct learning models on dynamic electrical material for class IX students of SMP Negeri 7 Sungai Raya.